Skema Citra dan Fungsi Metafora Ontologis pada Lirik Lagu “Huwa Al-Quran” - Nisa*, Siti Nuraini Wahidatun; Nur, Tajudin (Universitas Suryakanca, 2024)
Ontological metaphor is a type of metaphor that interprets things that have abstract processes by describing them as something physical. This article will describe the form and function of the ontological metaphor contained in the lyrics of the song